Race and time : American women's poetics from antislavery to racial modernity - Gray, Janet (Women's studies professor) (Book collections on Project MUSE., 2004)
Race and Time urges our attention to women's poetry in considering the cultural history of race. Building on close readings of well known and less familiar poets-including Elizabeth Margaret Chandler, Sarah Louisa Forten, Hannah Flagg Gould, Frances Ellen Watkins Harper, Sarah Piatt, Mary Eliza Tucker Lambert, Sarah Josepha Hale, Eliza Follen, and Mary Mapes Dodge-Gray traces tensions in women's literary culture from the era of abolitionism to the rise of the Plantation tradition. She devotes a chapter to children's verse, arguing that racial stereotypes work as "nonsense" that masks conflicts